ESCALATION OF THE AZERBAIJANI-ARMENIAN CONFLICT IN NAGORNO-KARABAKHAND THE POSITION OF INTERNATIONAL ACTORS (Вісник: Міжнародні відносини, 2024)
A new stage in the escalation of the Azerbaijan Armenia conflict, which occurred in late summer – early autumn 2022, is considered, and its impact on the future nature of interstate relations in the South Caucasus region and on the future of the peaceful settlement of the armed conflict is analysed. In addition, both the interests of global actors in the region, in particular the United States of America, the Russian Federation, the European Union, etc., and their intentions to benefit from the conflict itself and / or its settlement are established. The negotiation process between Azerbaijan and Armenia, which is mediated by both the EU and Russia, is also characterized.
Keywords: armed conflict, Azerbaijan-Armenia conflict, aggravation, USA, Russia, Turkey, South Caucasus, Zangezur corridor, Nagorno- Karabakh, negotiations, instability, sphere of influence